Oscillating gradient diffusion MRI reveals unique microstructural information in normal and hypoxia‐ischemia injured mouse brains. Issue 5 (28th August 2014) - Wu, Dan; Martin, Lee J.; Northington, Frances J.; Zhang, Jiangyang
<x xml:space="preserve">Abstract</x> Purpose We investigated whether oscillating gradient diffusion MRI (dMRI) can provide information on brain microstructural changes after formaldehyde fixation and after hypoxic‐ischemic (HI) injury beyond that provided by conventional dMRI. Methods Pulsed gradient spin echo (PGSE) and oscillating gradient spin echo (OGSE) dMRI of the adult mouse brain was performed in vivo (50–200 Hz, b = 600 mm2/s), and a similar protocol was applied to neonatal mouse brains at 24 h after unilateral hypoxia‐ischemia. Animals were perfusion fixed with 4% paraformaldehyde for ex vivo dMRI and histology. Results Apparent diffusion coefficients (ADCs) measured in the live adult mouse brain presented tissue‐dependent frequency‐dependence. In vivo OGSE‐ADC maps at high oscillating frequencies (>100 Hz) showed clear contrast between the molecular layer and granule cell layer in the adult mouse cerebellum. Formaldehyde fixation significantly altered the temporal diffusion spectra in several brain regions. In neonatal mouse brains with HI injury, in vivo ADC measurements from edema regions showed diminished edema contrasts at 200 Hz compared with the PGSE results. Histology showed severe tissue swelling and necrosis in the edema regions. Conclusion The results demonstrate the unique ability of OGSE‐dMRI in delineating tissue microstructures at different spatial scales. Magn Reson Med 72:1366–1374, 2014. © 2014 Wiley Periodicals, Inc.